ANALISIS PELAYANAN PENDIDIKAN INKLUSI ANAK DISGRAFIA STUDI KASUS PADA SISWA KELAS III SD - Muhammad Zulfikar Amiruddin (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
This study aims to find out the factors that cause children to become disgrafia and find out the services provided to disgrafia children in class III elementary school 2 Klepu Semarang. This research uses qualitative types and case study designs. The research sample was a special needs student in class III of Klepu State Elementary School 02 Pringapus District, Semarang Regency. The data collection methods used are interviews, observations, documentation and field records. The results of this study show that educational services provide several inclusion education programs to overcome children with learning problems which include the use of media that support children to be more interested in learning and also curriculum modifications carried out by classroom teachers along with special accompanying teachers. In addition, there are several factors that cause children to have learning difficulties due to the lack of attention that parents give to children. As well as the absence of communication between teachers and parents in overcoming difficulties in learning to write children.